EU Member States at the UN: A Case of Europeanization Arrested?*. (29th November 2016) - Smith, Karen E.
Abstract: This article addresses two questions about the EU's and EU Member States' diplomacy in the UN General Assembly's Third Committee and the Human Rights Council: have EU Member States been more, or less, active outside the framework of EU co‐ordination since the entry into force of the Lisbon Treaty? Has EU activity increased? The findings are that EU Member States have been increasingly active at the Human Rights Council and have increasingly worked with other states outside of the EU, while the level of EU activity has remained largely the same. In the Third Committee, Member States speak more than the EU but neither the EU nor Member States have been sponsoring more resolutions. Europeanization is 'arrested' in these cases, as Member States are reluctant to push for more EU activity because both the internal intergovernmental decision‐making system and external context discourage it.